Snow White and Rose Red - Grimm, Jacob (Englewood Cliffs, N.J. Prentice Hall, 1984)
A bear, befriended by two sisters during the winter, returns one day to reward them royally for their kindness.
Keywords: Fairy tales; Folklore -- Germany; Grimm, Jacob -- 1785-1863; Grimm, Wilhelm -- 1786-1859